1992
DOI: 10.1111/j.1467-9280.1992.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience and Emotional Development: The Emergence of Wariness of Heights

Abstract: Because of its biological adaptive value, wariness of heights is widely believed to be innate or under maturational colltrol. In this report, we presellt evidence colltrary to this hypothesis, and show the importance of locomotor experience for emotional developmellt. Four studies bearing on this conelusion ha\'e SIIOWII that (1) when age is held constant, locomotor experience accounts for wariness ofheights; (2) "artificial' , experience locomoting in a I~'alker generates evidence ofwariness of heights; (3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 11 publications
8
112
0
1
Order By: Relevance
“…Infants' experiences of fear might also dramatically increase later in the first year, again perhaps due to locomotion, which has been found to contribute to the emergence of a fear of heights (Campos, Bertenthal, & Kermoian, 1992). Locomotion also takes infants farther away from caregivers, which might lead to an increased sense of insecurity and fear.…”
Section: B the Negativity Bias In Emotional Contagionmentioning
confidence: 99%
“…Infants' experiences of fear might also dramatically increase later in the first year, again perhaps due to locomotion, which has been found to contribute to the emergence of a fear of heights (Campos, Bertenthal, & Kermoian, 1992). Locomotion also takes infants farther away from caregivers, which might lead to an increased sense of insecurity and fear.…”
Section: B the Negativity Bias In Emotional Contagionmentioning
confidence: 99%
“…For example, the emergence of rhythmic arm shaking of a rattle is associated with infant reduplicated babbling (e.g., Iverson, Hall, Nickel, & Wozniak, 2007), and the acquisition of upright sitting is related to infant perceptual completion of partially occluded objects (Soska, Adolph, & Johnson, 2010). A number of studies have also demonstrated the relation of infant self-produced locomotor experience (through crawling or experience in an infant walker) with a broad array of psychological phenomena, including cognitive development (Bertenthal, Campos, & Barrett 1984;Bai & Bertenthal, 1992), development of spatial search (Kermoian & Campos, 1988), perceptual development (Higgins, Campos, & Kermoian, 1996), social development (Campos, Kermoian, & Zumbahlen, 1992), emotional development (Campos, Bertenthal, & Kermoian, 1992), and neurophysiological processes (Bell & Fox, 1996). Experimental studies have demonstrated that some of the above relations are caused by locomotor experience, specifically by randomly assigning prelocomotor infants to a condition in which infants control a powered-mobility device and others do not (Dahl et al, in press;Uchiyama et al, 2008).…”
Section: Motoric Transitions As Epigenetic Phenomenamentioning
confidence: 99%
“…Gibson & Walk, 1960), 7-month-olds who are experienced crawlers often refuse to cross, and their heart rates accelerate (a sign of fear) when they are urged to do so. However, babies of the same age who are not yet crawling do not show signs of fear (Campos, Bertenthal, & Kermoian, 1992). The crucial difference seems to be the experience of self-generated locomotion, rather than crawling per se.…”
mentioning
confidence: 99%